ANALYSIS OF FACTORS AFFECTING INDONESIAN SUGAR IMPORTS FROM THAILAND BEFORE AND AFTER THE ATIGA ACCEPTANCE - I Gusti Made Krisna Arimbawa; Ni Luh Karmini (Adisam Publisher, 2024)
International trade has a close relationship with imports. In carrying out import activities there are price, production, consumption and exchange rate factors in a country. Apart from that, trade integration also has harmony in the occurrence of import activities by a country, especially in Indonesia, which is part of the ASEAN agreementTrade in Goods Agreement(ATIGA). By paying attention to the determining factors that influence imports, it will have an impact on a country's economic balance. The aim of this research isanalyze the factors influencing Indonesian sugar imports from Thailand before and after the ATIGA was agreed. This research was conducted in Indonesia with 28 years of observations in the period 1995-2022. The dependent variable in this research is Indonesian sugar imports from Thailand, while the independent variables consist of domestic sugar prices, domestic sugar production, domestic sugar consumption, the rupiah exchange rate against the USD, and the ASEAN Trade in Goods Agreement (ATIGA) as a dummy variable. The data used is secondary data with a data collection method, namely non-behavioral observation. This research uses descriptive analysis techniques and multiple linear regression analysis. The results of this research show that domestic sugar prices, domestic sugar production, domestic sugar consumption, the rupiah exchange rate against the USD, and the ASEAN Trade in Goods Agreement (ATIGA) simultaneously have a significant influence on Indonesian sugar imports from Thailand. Domestic sugar prices and the ASEAN Trade in Goods Agreement (ATIGA) partially have a positive and significant effect, domestic sugar production partially has a negative and significant effect, domestic sugar consumption partially has a positive and insignificant effect, and the rupiah exchange rate against the USD partially negative and insignificant effect on Indonesian sugar imports from Thailand. The implication of this research is that the factors that influence imports are very important to pay attention to, because these factors are related to each other which will increase or decrease the value of imports themselves.